Practical fluid mechanics for engineering applications - Bloomer, John J. (Mechanical engineering (Marcel Dekker, Inc.), 2000)
Provides the definition, equations and derivations that characterize the foundation of fluid mechanics utilizing minimum mathematics required for clarity yet retaining academic integrity. The text focuses on pipe flow, flow in open channels, flow measurement methods, forces on immersed objects, and unsteady flow.